Couples with intellectual disability where one partner has dementia – a scoping review exploring relationships in the context of dementia and intellectual disability - Jacobs, Paula (Ageing Soc, 2024)
Relationships and marriages between couples with intellectual disability are to be celebrated, as is the longer life expectancy now enjoyed by many with intellectual disability. However, dementia disproportionately affects people with intellectual disability, especially people with Down’s syndrome. Research into experiences of couples without intellectual disability who are affected by dementia suggests that a relational perspective provides health and social care professionals with information to support the wellbeing of both partners. This dyadic perspective is missing for couples with an intellectual disability where one partner has dementia. There is currently no evidence base informing how each partner may best be supported. This scoping review, with three separate searches, aims to address this gap. The first search sought to establish if any studies had explored the experiences of couples with intellectual disability where one partner has dementia. After determining that no studies have been published to date, the review explores what is known about relationships in the context of dementia (n=8) and in the context of intellectual disability (n=10), in second and third searches. Different ways to approach care and support in relationships among partners, staff and other family members were identified and it was evident that support could act as a facilitator as well as a barrier to people and their relationships. While the lives of couples affected by dementia appeared to remain largely private, couples with intellectual disability had a high involvement of staff and family members in their life. Potential implications for future research with couples with intellectual disability affected by dementia are discussed, highlighting the importance of exploring how couples navigate emotional complexities and changes in their relationship, while understanding that the context in which the lives of people with intellectual disability take place and relationships happen is different.